Development of productivity database for construction - Ueki, Misaki C.
Productivity databases provide input for decision making in scheduling and cost-estimation of a construction project. Since there is no available productivity database in the Philippines that is accessible to everyone, this study can potentially benefit small and medium local construction companies, as well as other researchers. The study employed two observational methods: (1) continuous observation in construction sites in Calamba City and Quezon City, and (2) intermittent observation method done by analyzing monitoring data of a local construction company's past projects. The mean actual rate (direct observation) was compared to the mean theoretical rates (time-motion study). The mean total rate from the direct observation method was compared to published data such as a local company's productivity database and Planning Planet. The deviation among the data is quantified by getting the percent difference. Recommended productivity rates were obtained from average productivity rates in direct observation method. Survey forms were distributed to licensed construction companies to assess the significance of different factors that affect productivity. Analyzing the gathered data yielded the Relative Importance Index and ranking of factors. The most and least significant factors affecting labor productivity were identified.